Baudelaire, le poète, l’étranger - Béryl Schlossman (Carnets)
The strange and the unknown are familiar figures in Baudelaire’s writing; they indicate the presence of a phenomenon or a being that give form to the poetic event. In Baudelaire’s poetry, his intimate journals, and his essays, however, the presence of strangers as such is very difficult to pin down – the stranger is nearly invisible. Given the focused vision of anonymity and the urban environment, the question arises of the hidden status of the stranger or foreigner in the modernity launched in Baudelaire’s writings. A reading catalyzed by «L’Etranger [The Stranger]», the first prose poem in Paris Spleen, traces the path of these enigmatic figures in the work of the great poet of Parisian modernity.